Child-parent research reimagined - Abrams, Sandra Schamroth; Schaefer, Mary Beth; Ness, Daniel, 1966- (Brill Sense, 2020)
"Child-Parent Research Reimagined challenges the field to explore the meaning making experiences and the methodological and ethical challenges that come to the fore when researchers engage in research with their child, grandchild, or other relative. As scholars in and beyond the field of education grapple with ways that youth make meaning with digital and nondigital resources and practices, this edited volume offers insights into nuanced learning that is highly contextualized and textured while also (re)initiating important methodological and epistemological conversations about research that seeks to flatten traditional hierarchies, honor youth voices, and co-investigate facets of youth meaning making. Contributors are (in alphabetical order): Charlotte Abrams, Sandra Schamroth Abrams, Kathleen M. Alley, Bill Cope, Mary Kalantzis, Molly Kurpis, Linda Laidlaw, Guy Merchant, Daniel Ness, Eric Ness, "E." O'Keefe, Alaina Roach O'Keefe, Joanne O'Mara, Anthony J. Onwuegbuzie, Sarah Prestridge, Lourdes M. Rivera, Dahlia Rivera-Larkin, Nora Rivera-Larkin, Mary Beth Schaefer, Cassandra R. Skrobot, and Bogum Yoon"--